БЫКОВАИТ, BANA{(NA,TI)4[(TI,NB)2(OH,O)3SI4OI4](OH,F)2 - Хомяков А.П.; Меньшиков Ю.П.; Феррарис Д.; Немет П.; Нечелюстов Г.Н. (My University, 2005)
New mineral bykovaite, a product of hydrothermal alteration of bomemanite, was found in hyperagpaitic pegmatite «Shkatulka» at Mount Alluaiv, Lovozcro alkaline massif (Kola Peninsula, Russia) occurring in association with ussingite, bomemanite, vuonnemite, shkatulkalitc, lomonosovite, steenstrupine-(Ce), belovite-(Ce), sphalerite, etc. It occurs as compact spherulites, up to 3 - 5 mm in diameter, and spherical aggregates of tiny (0.005 - 0.05 mm) fibers radiating along [010] from a common center. The mineral is creamy with white streak and silky luster. Scmitransparent. Brittle, cleavage is perfect on {001} and good on {100}. Mohs* hardness 3. Density measured - 2.98, calculated - 2.72 g/cm3. Slowly decomposed by 10 % HC1 and HNO3. Optically biaxial positive, JV,= 1.668, Nm = 1.679, Ng= 1.710, 2K(meas.)= 63(5)°, 2K(calc.) = 63°. Thermal data and IR spectrum are given. Chemical composition, by electron microprobe analysis (H2O by TGA weigh loss), includes Na2O 13.34, K2O 0.67, CaO 0.20, SrO 0.66, BaO 13.22, FeO 0.28, MnO 2.22, A12O3 0.15, SiO2 29.05, TiO2, 18.93, Nb2O5 10.75, F 1.40, H2O 10.00, -O = F2 0.59, total 100.28 wt%. The empirical formula based on Si + Al= 4 and in accordance with the modeled structure of the mineral is as following: 2.32H2O. Idealized crystal chemical formula is BaNa{(Na3Ti)[(TiNb)(O2OH)Si.,Oi4] (OH,F)2} 3H2O. Monoclinic, space group /116, a 5.552 (1), b 7.179 (1), с 50.94 (1) А, у 91.10 (1)°, P2030 (1) A3, Z = 4. The strongest XRD lines [d, A (IK»*/)]: 25.50 (100)(002); 3.17(74)(0.0.16); 8.48 (72)(006); 2.763 (20)(127, 202, 0.2.12); 12.68 (14)(004); 3.44(14)(0.1.13); 2.110 (14)(0.0.24, 0.1.23, 136, 226); 5.11 (11)(017); 3.55 (10)(1.0.11, 022). Bykovaite has a modular heterophyllosilicate crystal structure that could be compared with that of bornemanite except the interlayer content. The mineral is named in memory of Alexandra Vasilievna Bykova (1917-2001), the well-known chemist-analyst of new minerals, who was the first to analyze bornemanite and to demonstrate experimentally the ability of bomemanitc to loose Na3PO4 after water treatment, thereby actually predicting existence of a natural hydratcd analogue of bornemanite. Type specimen is deposited in the Mining Museum of the St. Petersburg State Mining Institute.
Keywords: 549.6